Mandatory corporate social responsibility: Law and policy in Indonesia - Sabela (2016)
This research is related to Constitutional Court Verdict Number 53/PUU-VI/2008 on Judicial Review of Article 74 of Company Liability Act Number 40/2007. The verdict officially and legally stipulates that mandatory CSR legal provision be made consistent with the Indonesian constitution. Therefore, the mandatory CSR legal provision is still part of Act Number 40/2007 of Limited Company Liability. The verdict was passed in 2008 but its realization was delayed since the Ministry for Justice and Human Rights passed Regulation Number 47/2012 on Social and Environmental Responsibility. This regulation is only executed four years after the regulation was released. During that period there was pro and contra debates among business associations, the government, CSR academics, and CSR based NGOs on the enactment of mandatory CSR legal provision. This research examines and analyzes the following key issues: (1) the philosopical rationale behind the enactment of mandatory legal provision, (2) the mandatory CSR standard of guidelines currently used by corporations, and (3) the functions, liabilities and jurisdiction of the mandatory CSR surveillance body in Indonesia. Using a qualitative approach, this study applies a content analysis as an analysis tool. Relevant data from journal articles, relevant books, Bill, and rules and regulations were collected. Additionally, some field data were collected from the interviews with thirty key CSR resource persons. These respondents consisted of academics, CSR-based NGOs, government officials, corporations, and business association representatives. The findings are as follows; the government of Indonesia should strengthen regulation on CSR by passing an Act on CSR, the establishment of CSR surveillance body is necessary, mandatory CSR rules, regulations, and guidelines are also important to be codified and passed by the Government and Indonesia Manual on Mandatory CSR is encouraged to be passed by the Government. Accordingly, this research significantly provides some recommendations on a comprehensive information dissemination of the enactment of mandatory CSR. It also suggests a proper mandatory CSR standard be outlined to suit the Indonesian context and complexity, and that better management functions, liabilities, and jurisdictions of the mandatory CSR surveillance body be strengthened in Indonesia. It is hoped that the findings would benefit the implementation of mandatory CSR legal provision and the drafting of a better mandatory CSR legal framework in the country.